2019
DOI: 10.21307/pjm-2019-014
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Colonization of the Large Intestine by Candida on the Treatment of Crohn’s Disease

Abstract: The aim of this study was to determine if there are quantitative differences in Candida fungi between pediatric patients with Crohn's disease (before and after exclusive enteral nutrition (EEN), and the biologic therapy with anti-tumor necrosis factor alpha-(IFX)), and healthy controls. DNA was isolated from fecal samples and PCR was used to determine the number of fungal cells. Both therapeutic interventions resulted in a statistically significant decrease in Pediatric Crohn's Disease Activity Index. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…A detailed DNA isolation protocol was presented in our team’s previous studies 16 . The frozen samples were thawed, precisely weighed (about 0.1 g of stool sample was used) and homogenized in 0.1 ml of saline.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed DNA isolation protocol was presented in our team’s previous studies 16 . The frozen samples were thawed, precisely weighed (about 0.1 g of stool sample was used) and homogenized in 0.1 ml of saline.…”
Section: Methodsmentioning
confidence: 99%
“…At the Department of Microbiology JUMC, Kraków, Poland, fungal DNA was isolated from 76 stool samples using the Genomic Mini AX Stool Spin kit (A&A Biotechnology, Gdańsk, Poland) with the application of a preliminary procedure, as described by us earlier [ 15 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The gut mycobiota composition seems to be influenced by diet, including consumption of carbohydrates, which correlate positively with fungi of the genus Candida [ 14 ]. Additionally, an effective biological treatment applied to children with Crohn’s disease (CD) resulted in reducing the number of fungi of the genus Candida in the colon of these patients, which may suggest their significance in the development and course of CD [ 15 ]. Analysis of the gut microbiome in patients with diabetes, also taking fungi into consideration, was also conducted, showing that fungi of the genera Aspergillus and Candida (opportunistic fungal pathogens) were overrepresented in newly diagnosed type 2 diabetic subjects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this line, Liguori et al, 57 and Sokol et al, 33 reported an increased abundance of C glabrata and C albicans in CD patients, respectively. Recently, Kowalska‐Duplaga et al, 107 presented the abundance of Candida in CD patients that decreased during the therapeutic intervention, particularly in patients who received anti‐TNF‐α treatment (infliximab).…”
Section: Mycobiome In Ibdmentioning
confidence: 99%